Limited surgery and conformal photon radiation therapy for pediatric craniopharyngioma: long-term results from the RT1 protocol. Issue 12 (12th May 2022) - Edmonston, Drucilla Y; Wu, Shengjie; Li, Yimei; Khan, Raja B; Boop, Frederick A; Merchant, Thomas E
Abstract: Background: Our aim was to estimate long-term disease control and complications after conformal radiation therapy (CRT) in children and adolescents with craniopharyngioma. Materials and Methods: Pediatric patients with craniopharyngioma (n = 101) were enrolled on or treated according to a phase II single institutional protocol from 1998. Surgery was individualized, and CRT (54Gy) was administered using a 1.0 cm or 0.5 cm clinical target volume margin. Patients were followed for 10 years by serial MR imaging and MR angiography and a battery of tests to measure the effects of treatment. Results: Twenty patients had tumor progression. Twelve patients who had tumor progression died due to tumor (n = 6) or complications related to tumor or treatment (n = 6). With a median follow-up of 14.94 years for survivors, the 10 year estimates (±SE) of progression-free survival (PFS), event-free survival (EFS), and overall survival (OS) were 78.84% ± 4.10%, 77.12% ± 4.19%, and 96.02% ± 1.95%, respectively. OS, EFS, and PFS were significantly associated with race, shunt status, and tumor volume. The 10 year cumulative incidence (±SE) of the secondary tumor (1.99% ± 1.40%), secondary malignant tumor (1.0% ± 1.0%), necrosis (1.98% ± 1.39%), vasculopathy (8.47% ± 2.90%), and permanent neurologic deficits (8.28% ± 3.37%) were estimated by competing risk analysis. Three patients required revascularization surgery. Salvage therapy was successful in 13 patients using surgery and radiosurgery. Conclusions: Limited surgery and CRT using photons results in excellent tumor control. Tumor control and the incidence and severity of complications are associated with host, tumor, and treatment factors.